Prognostic Significance of HPV Status in Laryngeal Squamous Cell Carcinoma: A Large-Population Database Study. (July 2021) - Panuganti, Bharat A.; Finegersh, Andrey; Flagg, Mitchell; Tu, Xin; Orosco, Ryan; Weissbrod, Philip A.; Califano, Joseph
Objective: To explore the survival implications of human papillomavirus (HPV) positivity and subtype in larynx cancer through a national cancer database. To investigate staging discrepancies in larynx cancer associated with HPV status. Study Design: Retrospective observational cohort study. Setting: National Cancer Database. Methods: Data were extracted concerning adults with known HPV status who were treated between 2010 and 2016 for laryngeal squamous cell carcinoma. Patients without known HPV subtype were excluded. Cox multivariable regression models were fit to evaluate the survival impact of HPV status, characterized as a binary variable (HPV+ vs HPV–) and by subtype. Two- and 5-year survival rates were calculated via the Kaplan-Meier method and compared by stage between the HPV+ and HPV– cohorts per the log-rank test. Results: Patients with HPV+ larynx cancer were younger (60.5 vs 64.3 years, P < .001), more likely to have private insurance (37.2% vs 31.2%, P < .001), more commonly White (84.6% vs 82.4%, P = .013), and more likely to present with nodal disease (42.6% vs 33.0%, P < .001). HPV positivity and HPV subtype 16 were associated with improved overall survival. One-stage discrepancies in 5-year survival were observed between the HPV+ and HPV– cohorts: stage II HPV+ (69.45%) vs stage I HPV– (65.77%); stage IV HPV+ (47.67%) vs stage III HPV– (46.80%). Conclusions: HPV positivity and infection with HPV subtype 16 are correlated with improved overall survival in patients with laryngeal squamous cell carcinoma, manifesting with a 1-stage incremental survival advantage. Future prospective studies are indicated to corroborate the findings from this large-population database retrospective study.